Desenvolvimento de membranas a partir da celulose da fibra e bagaço de sisal com diferentes aplicações biotenológicas - Xavier, Franklin Damião (2023)
Membrane development plays a key role in recovery and purification in biorefining and bioenergy processes. The membranes provide excellent fractionation and separation capabilities, low consumption of chemical reagents and reduced energy costs. Many types of materials are being tested as candidate precursors for membrane production. The use of agro-industrial residues and low-cost biomass are increasingly recurrent proposals, as they are cost-effective materials and are widely available in nature. Lignocellulosic biomass plays a major role in this context, among them Agave Sisalana, which in the constitution of its fibers has about 80% of carbohydrates. In addition to the fiber, other parts of sisal can be used in the membrane manufacturing process, such as sisal bagasse, which has no commercial applicability and is discarded in the environment. In the present work, the potential of sisal fiber and bagasse for the production of organic membranes, their optimal synthesis conditions and efficiency in the removal of fermentative inhibitors from the biotechnological production of alcohols were evaluated. The biomass underwent physical treatments of drying and milling. Then, its lignocellulosic composition was determined and cellulose was isolated. Cellulose was acetylated to obtain cellulose triacetate. For the synthesis of the membranes, cellulose triacetate from the fiber and sisal bagasse were used together with different organic solvents by the phase inversion method. In the best condition obtained, cellulose was produced with 1.3% of residues for the fiber and 10% for the sisal bagasse in the acid and alkaline pre-treatment. The cellulose acetate produced had a degree of substitution of 2.89 and 2.58 respectively; both being characterized as high purity cellulose triacetate. Using the phase inversion method the membranes were synthesized, the acetone derivatives were not formed, probably due to poor dissolution of the polymeric matrix in the solvent. Membranes derived from dichloromethane showed an opaque surface for sisal bagasse and a translucent surface for the fiber. The membranes produced in the present work show excellent furfural retention results, with more than 90%, and satisfactory results for acetic acid recovery. According to the retained inhibitor molecules and taking into account the physical properties determined by SEM, porosity and permeate flux, it is possible to suggest the application of the synthesized membranes in ultra and microfiltration processes.